Students' attitudes to the implementation of vocabulary learning strategies in writing task - Zuraina, Ali; Mehr, Samira Ahmadi; Tilwani, Shouket Ahmad; Noraisah Nurul Fatwa, Mohd Razali; Alia Najaa, Md Nor; Norsuhaily, Abu Bakar (Sciedu Press, 2022)
Vocabulary is paramount in language learning. Learners can strategize vocabulary learning using vocabulary learning strategies (VLS), namely memory, cognitive compensation, metacognitive, social, affective, and determination. If used appropriately, VLS can help learners in writing. The study investigates the level of students' attitudes and use of VLS in writing. Also, it examines the male and female students in their attitudes and the use of VLS in writing. Finally, it investigates students' attitudes in writing according to their English grades. A quantitative research method, namely a survey, was employed as the research design in the study. It employed 71 diploma students taking engineering majors in one of the technical universities on the East Coast of Malaysia. The study found that students demonstrated a moderately high attitude in writing but moderately low VLS scores. There was also no significant difference in the attitudes and use of VLS between genders. Finally, there was insufficient evidence to show a significant difference in attitudes and English grades. Nevertheless, the study implied a need to familiarize the students with VLS to improve their writing skills. However, students were not required to use all the VLS as some VLS might be appropriate for a particular task but not the others.